Electroless plating fundamentals and applications - Mallory, Glenn O.; Hajdu, Juan B. (AESF ; Noyes Publications/William Andrew Pub., 1990)
Describes the chemical principles of the major electroless processes and applications of these techniques in the industry.
Originally published: Orlando, Fla. : American Electroplaters and Surface Finishers Society, c1990.
Keywords: Electroless plating.; elektronické knihy; electronic books